GAMBARAN TINGKAT PENGETAHUAN TENTANG PENULARAN DAN PENCEGAHAN COVID-19 PADA PEGAWAI FK UMSU - HUTAGALUNG, ARI SATRIA; LUBIS, DEBBY MIRANI (LP2MTBM MAKARIOZ, 2024)
A mysterious case of pneumonia was first reported in Wuhan, this disease is called Covid-19. The virus can be transmitted from person to person and has spread widely in China and more than 190 other countries and territories. The World Health Organization declared SARS-CoV-2 a pandemic, as of March 29, 2020, there were 634,835 cases and 33,106 deaths worldwide. Meanwhile, in Indonesia, 1,528 cases have been determined to be positive for Covid-19 and 136 deaths. The purpose was to find out an overview of the level of knowledge about the transmission and prevention of Covid-19 in FK UMSU employees. The method used is observational descriptive with a cross-sectional approach. The sample used in this study was 37 respondent FK UMSU employees. The results are based on research on the overview of the level of knowledge about the transmission and prevention of Covid-19 conducted on 37 respondents, all respondents in the well-informed category. Based on the characteristics of the respondents, the level of knowledge of Covid-19 in FK UMSU employees is good and the level of knowledge about the transmission and prevention of Covid-19 in FK UMSU employees is good.